Supplementary Table for "The Plasma Metabolomic Profile is Differently Associated with Liver Fat, Visceral Adipose Tissue, and Pancreatic Fat" - Lind, Lars (Uppsala University, 2020)
Data (tables) associated with the manuscript "The Plasma Metabolomic Profile is Differently Associated with Liver Fat, Visceral Adipose Tissue, and Pancreatic Fat" by Lind et al. 2021.

Context: Metabolic differences between ectopic fat depots may provide novel insights to obesity-related diseases.

Objective: To investigate the plasma metabolomic profiles in relation to visceral adipose tissue (VAT) volume and liver and pancreas fat percentages.

Design: Cross-sectional.

Setting: Multicenter at academic research laboratories.

Patients: Magnetic resonance imaging (MRI) was used to assess VAT volume, the percentage of fat in the liver and pancreas (proton density fat fraction [PDFF]) at baseline in 310 individuals with a body mass index ≥ 25 kg/m2 and with serum triglycerides ≥ 1.7 mmol/l and/or type 2 diabetes screened for inclusion in the 2 effect of omega-3 carboxylic acid on liver fat content studies.

Intervention: None.

Main outcome measure: Metabolomic profiling with mass spectroscopy enabled the determination of 1063 plasma metabolites.

The dataset was originally published in DiVA and moved to SND in 2024.

Data (tabeller) tillhörande manuskriptet "The Plasma Metabolomic Profile is Differently Associated with Liver Fat, Visceral Adipose Tissue, and Pancreatic Fat" av Lind et al., 2021. Se engelsk version av katalogposten för info om studien.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Supplementary Table for "The Plasma Metabolomic Profile is Differently Associated with Liver Fat, Visceral Adipose Tissue, and Pancreatic Fat"
Keywords: liver fat; liver fat; pancreatic fat; pancreatic fat; obesity; obesity; metabolomics; metabolomics; MRI; MRI; Ectopic fat; Ectopic fat; Medical and Health Sciences; Medicin och hälsovetenskap